2010
DOI: 10.1002/ange.201005585
|View full text |Cite
|
Sign up to set email alerts
|

A Stabilizing Influence: CAL PDZ Inhibition Extends the Half‐Life of ΔF508‐CFTR

Abstract: Recycling lohnt sich! Die am häufigsten auftretende Mutation bei Mukoviszidose verhindert die Reifung und beschleunigt den Abbau des Ionenkanals CFTR. Ein Stabilisator wird vorgestellt, der eine für den CFTR‐Abbau verantwortliche PDZ‐Domäne blockiert. Der Hemmstoff iCAL36 verlängert die Halbwertszeit des Chloridkanals in bronchialen Epithelzellen. Er ergänzt außerdem die Aktivität eines Faltungskorrektors und erfüllt damit eine Voraussetzung für kombinierte Mukoviszidosetherapien.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Plates were allowed to equilibrate 15 min at 24°C before measurement. Fitting was performed as described (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plates were allowed to equilibrate 15 min at 24°C before measurement. Fitting was performed as described (13).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that the plasmamembrane half-life and cell-surface abundance of CFTR can be stabilized by inhibition of the CFTR-associated ligand CAL or by depletion of the ubiquitin ligase c-Cbl (13,14). Although several proteins involved in the uptake process have been identified (15), their roles are incompletely defined in polarized airway epithelial cells.…”
mentioning
confidence: 99%
“…In the Golgi, modulation of the function or abundance of PDZ-domain containing proteins has been shown to correct ⌬F508CFTR trafficking (10,22,23). Similarly, EBP50 has been implicated in r⌬F508CFTR biosynthetic processing.…”
mentioning
confidence: 99%
“…We and others have shown that plasma membrane abundance of CFTR is regulated by a number of PDZ proteins, including NHERF1/EBP50, NHERF2, and CFTR-associated ligand (1,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). A common feature of these proteins is the presence of a PDZ (PSD-95, Dlg, ZO-1) domain, a protein-protein interaction module that engages the C terminus of CFTR.…”
Section: Sgk1 Does Not Phosphorylate Cftr-although Cftr Doesmentioning
confidence: 99%